A study on the vocational-agricultural school libraries in Leyte - Jaime, Consuelo B. (1982)
This study which generally aimed to describe in a comparative perspective the vocational-agricultural school libraries in Leyte in terms of their personnel, finance, building, facilities and equipment, collection as well as services and use, also attempted to identify the common problems confronting them and to evolve some practical solutions, suggestions and recommendations that may redound to the improvement of their various services as well as their ultimate development in the future.